Intracellular delivery of biomineralized monoclonal antibodies to combat viral infection. Issue 9 (17th December 2015) - Song, Zhiyong; Liu, Long; Wang, Xiaoyu; Deng, Yongqiang; Nian, Qinggong; Wang, Guangchuan; Zhu, Shunya; Li, Xiaofeng; Zhou, Hangyu; Jiang, Tao; Xu, Xurong; Tang, Ruikang; et al.
Abstract : Conventional therapeutic monoclonal antibodies (mAbs) are invalid for intracellular viruses but by using in situ biomineralization treatment, they can be successfully delivered into cells to inhibit intracellular viral replication. Abstract : Conventional therapeutic monoclonal antibodies (mAbs) are invalid for intracellular viruses but by using in situ biomineralization treatment, they can be successfully delivered into cells to inhibit intracellular viral replication. This achievement significantly expands the applications of mAbs and provides a new intracellular strategy to control viral infections.